Long-range oxygen ordering linked to topotactic oxygen release in Pr2NiO4+δ fuel cell cathode material. Issue 28 (8th July 2020) - Dutta, Rajesh; Maity, Avishek; Marsicano, Anna; Ceretti, Monica; Chernyshov, Dmitry; Bosak, Alexeï; Villesuzanne, Antoine; Roth, Georg; Perversi, Giuditta; Paulus, Werner
Abstract : Complex oxygen ordering evidenced for the oxygen membrane cathode material Pr2 NiO4.25 at room temperature with translational periodicities attaining almost 100 Å by single-crystal synchrotron diffraction studies. Abstract : Solid oxide ion conductors are technologically important for oxygen membranes, sensors and solid oxide fuel cells (SOFC). However, oxygen diffusion is a thermally activated process, and materials operating at ambient temperature are rare, as the related diffusion mechanisms are poorly understood. Herein, we report a hidden spontaneous oxygen release reaction that interconverts two stoichiometric phases of the SOFC material Pr2 NiO4+ δ with unprecedented structural complexity at ambient temperature. A slight change in the oxygen stoichiometry from δ = 0.25 to δ = 0.225 involves a transition between two competing modulated superstructures, showing long-range translational periodicities up to 94 Å. Our findings demonstrate correlated oxygen diffusion within the bulk phase at room temperature, which is accompanied by the formation of long-range modulated superstructures up to the lower mesoscale. Large-scale ordered structures found here for Pr2 NiO4+ δ are rather indicative of non-local interactions, and are interpreted to be mediated via structural deformations. This unexpected behavior is discussed in terms of an unconventional understanding of low- T oxygen diffusion mechanisms and its potential to conceive and optimize oxygen ion conductors, which are an important class of compounds relevant to technological applications.